Men on the market: Feminist analysis of age-stratified male–male romance in Boys' Love manga. Issue 2 (1st December 2016) - Madill, Anna
Male–male sexuality is the central trope of Boys' Love (BL) manga with stories tending to revolve around a central uke-seme ('bottom'–'top') pair. Although focused on men, BL is produced and consumed primarily by women. This article presents, from an anglophone British perspective, analysis of age-stratified male–male romance – paederasty – as portrayed in BL. My corpus consists of 234 commercially-translated original Japanese BL manga stories, created by 100 different mangaka (author-artists), published commercially in English between 2003 and 2012. A total of 68 (30%) of these stories were identified as involving agestratified relationships, eight of which were selected for detailed analysis. Seven were selected for typicality: Waru (2007) by Yukari Hashida deemed the most typical. Fangs (2008) by Hiroki Kusumoto was also included in analysis as the most atypical age-stratified story in order to test the robustness of identified patterns. I argue that that, from an anglophone perspective, the characteristic themes of age-stratified BL map surprising well onto the eroticised intra-familial dynamics of Freud and the intra- and inter-familial economics of Lévi-Strauss. The patterns identified are evidenced and discussed under the following headings: the mother identified son, the doubly divested man, the castrated father, men on the market and the mother with the phallus. These themes help build and substantiate my argument that age-stratified BL might work, within an anglophone context at least, as a feminist critique of patriarchy through the mechanism of phallic divestiture.